Zambia : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The report provides details of IMF estimates on basic indicators, GDP by sector of origin at constant and current prices, index of industrial production, marketed production of selected crops, annual average and monthly composite index of consumer prices, fuel prices and mineral production details, electricity generation and consumption, national pension scheme authority operations, summary of accounts of the Bank of Zambia (BOZ) and commercial banks, structure of interest rates, merchandise exports and imports by Standard International Trade Classification (SITC), imports and exports by the country, central government external debt, summary of consolidated the foreign exchange market, et cetera.